Precipitation and temperature anomalies over Aotearoa New Zealand analysed by weather types and descriptors of atmospheric centres of action. (22nd June 2022) - Pohl, Benjamin; Sturman, Andrew; Renwick, James; Quénol, Hervé; Fauchereau, Nicolas; Lorrey, Andrew; Pergaud, Julien
Abstract: Weather types (WTs) are often used to assess the relationships between synoptic‐scale atmospheric dynamics and local scale climate anomalies. We focus here on Aotearoa New Zealand (ANZ) where pre‐existing WTs have recently been characterized using a set of descriptors monitoring the daily location and intensity of their main atmospheric centres of action (ACAs). We show here that the precipitation and temperature anomalies associated with the WTs in ANZ are more complex than previously thought. They do not solely depend on type occurrence, but are also strongly modulated by within‐type changes in the location and intensity of ACAs, and their interaction with surface terrain. Thus, the mere analysis of WT occurrence is not sufficient to explain climate variability over ANZ. The magnitude and sign of daily minimum and maximum temperature anomalies are strongly driven by meridional advection of temperature, which is also driven by within‐type changes in ACAs. The amplitude of precipitation anomalies is likewise strongly variable within WTs. Associated mechanisms involve interactions between the underlying terrain and atmospheric fluxes modulated by ACAs, modifying the strength and location of orographic uplift. Finally, daily extreme precipitation can occur under several cyclonic WTs, more particularly when their low‐pressure ACAs are significantly more intense than normal. This situation is associated with more intense moisture transport towards ANZ, promoting heavy precipitation there. These results provide a detailed assessment of within‐type variability in temperature and precipitation patterns at both synoptic and local scales. They also help to improve understanding of local effects of larger scale synoptic patterns, thereby allowing for more accurate use of analogues in forecasting. Abstract : From synoptic conditions (1) to local anomalies of surface variables (2), and associated mechanisms driving their variability (3).